Comparison of two different warm up program (stretching and massage) on sprinting performance among footballer / Ahmad Afnan Mat Zlan - Mat Zlan, Ahmad Afnan (2019)
The aim of this study is to determine the effect of two different types of warm up program which is static stretching and Swedish massage on sprinting performance among footballer. Twenty male footballers volunteered to participate in this study. All of the from Sultan Abu Bakar School age 14.50 ±1.00 years, weight 55.13 ±14.98 kg and height 165.75 ± 6.40 cm. This study had one group post test only experimental design. This study had two sessions which were apart two days each session and the instrumentation that involved in this study was 20 meters and 100 meter dash. All subjects need to perform static stretching warm up for the first session and take the test which was 20 meter and 100 meter dash with active rest for four minutes between tests. Next, subjects need to perform Swedish massage program apart for two days after the first session with active rest between tests. All the result was recorded using stopwatch. The data show there were significant after applying static stretching on 20 meters and 100 meter dash. The finding showed that the result of 20 meter dash with t(19) = 58.338 p< 0.05. Meanwhile, the result for 100 meter dash is t(19) = 69.385 p < 0.05. Hence, this study rejected the null hypothesis. Next, the data also showed there were significant effect after applying Swedish massage on 20 meters and 100 meter dash. The finding showed that the result of20 meter dash with t(19) = 66.830 p< 0.05. Meanwhile, the result for 100 meter dash is t(19) = 50.384 p < 0.05. Hence, this study also rejected the null hypothesis. Besides, the results also showed there were significance differences on comparison between two different warm up program on 20 meters and 100 meter dash. The result for 20 meter dash is t(19) = 5.718 p < 0.05. Meanwhile the result for 100 meter dash is t(19) = 4.631 p < 0.05. There were positive improvement after applying static stretching while the adverse effect occurs when apply Swedish massage on the lower limb. Therefore, it was recommended that static stretching more suitable for warm up before competition because this type of warm up can boost performance than Swedish massage.